Islamic prenatal education for pregnant mothers in ngadirojo village - Mohamad Ardin Suwandi; Fatikhatul Muawanah (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
Prenatal education is one of the important stages in forming a child's character. This education starts from the time the fetus is in the womb until it is born into the world. Many mothers do not carry out their duties properly in providing stimulus or stimulation to the child they are carrying because of the mother's lack of knowledge about how to educate a child well while still in the womb in the Islamic view and there are still many who think that the child's intelligence and intelligence is sufficiently supported by nutrition. the good one. This research aims to reveal the concept of prenatal education from the perspective of Islamic religious education. The research method used is a qualitative research method with a qualitative descriptive approach. Data was obtained through literature studies and interviews with pregnant women in local villages. Data analysis was carried out using observation and interview techniques. The research results show that further research is still needed to develop more specific and measurable Islamic-based prenatal education methods. It is hoped that collaboration between educators, health practitioners and ulama can produce a more holistic and effective approach to Islamic-based prenatal education. The research results show that prenatal education from the perspective of Islamic religious education involves aspects such as the habit of listening to the holy verses of the Koran, prayers and dhikr which are good for fetal development. Apart from that, it is important to provide positive stimulation and a conducive environment for pregnant women. The novel elements in this research are the role of parents in prenatal education, the influence of the environment on pregnancy, prayer and dhikr during pregnancy, early religious education, health and nutrition in Islam, the role of society and community. It is hoped that the results of this research can contribute to the understanding of the importance of prenatal education in Islam, so that it can serve as a guide for pregnant mothers in preparing a quality generation.